2016
DOI: 10.1002/pat.3968
|View full text |Cite
|
Sign up to set email alerts
|

Radiation crosslinked Polyolefinic blends: exploring thermally tuned dual Shape Memory character

Abstract: Shape memory behavior of thermally triggered polymeric materials based on ethylene octene copolymer (EOC) and ethylene propylene diene rubber (EPDM) has been studied in details. Investigation of the shape memory behavior of uncrosslinked EOC-EPDM and electron beam crosslinked EOC-EPDM blends have been pursued thoroughly. Shape memory study has been carried out at 60°C, which shows that with the effect of electron beam radiation shape fixity behavior of the crosslinked blends becomes poor as compared with its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Presence of crosslinked network improves the shape recovery behavior, decrease the shape recovery induction time, and so forth. of SMP blends . Several shape memory polymer blends have been reported by several authors including polyethylene/polycyclooctene , PVDF/PMMA , SBS/PCL , and EOC/EPDM .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Presence of crosslinked network improves the shape recovery behavior, decrease the shape recovery induction time, and so forth. of SMP blends . Several shape memory polymer blends have been reported by several authors including polyethylene/polycyclooctene , PVDF/PMMA , SBS/PCL , and EOC/EPDM .…”
Section: Introductionmentioning
confidence: 98%
“…In their previous work , authors have reported the shape memory character of the EOC‐EPDM blends system. The author has studied distinguishedly the shape meomory behavior of the blend both in the uncrosslinked and crosslinked (by electron beam) state.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts were made to adjust the temperature range of T g of SMPs. There are some studies on rubber‐based SMPs . Most of them were prepared by blending plastic and rubber and tailoring the ratio of rubber/plastic to tailor T g and gain excellent SMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer blending is one of the cheapest methods of tailoring polymeric materials for specific applications. The gain in new properties depends on the degree of compatibility or miscibility of the polymers in the intermolecular level …”
Section: Introductionmentioning
confidence: 99%